Blockchain technology application in a refuse management system - Sham, Rohana; Amir Hussin, Amir 'Aatieff; Abdamia, Noranita; Mohamed, Suhana; Musa, Omar; Rasi, Raja Zuraidah (IEEE, 2020)
The blockchain mechanism in managing refuse management for a household, is much needed to facilitate peer to peer exchange of data and consent within the community. This can be publicly accessible yet very secure using unanimous user authentication protection system through the blockchain mechanism. Therefore, the main aim of the study is to identify why blockchain should be used as mechanism in the refuse management system in an urban area and to propose a new model of the pollution-free environment through blockchain technology. The research embarks into a qualitative method where simulation and observation were carried out to examine the current situation. The ultimate outcome is to produce a pollution-free environment by integrating the blockchain mechanism in the refuse management system for the utilization of the surrounding community.